The angel of death: the non-progressive subject of architectural history - Basson, Steve (Society of Architectural Historians, Australia and New Zealand, 2003)
For architectural history, progress represents the conceptual authority that ties the past to the present; that allows each age to act as the natural outcome of what preceded it and in anticipation of what would follow; and that secures a logical, continuous and trans-historical vision of architecture's historical being. But what can be said to lie in the wake of these progressive drives across the landscapes of architecture's past is a trail of destruction, realized through a linear sequencing of periods subsumed to a predetermined order of existence denying any autonomy of voice or conditions of architectural identity, purpose and rationality. It is in the terms of what Benjamin referred to as the storm and violence of progress, Bergson of the absurdity of teleology and Nietzsche of the congenital defects of the aeterna veritas, that to speak of progress is to embrace a history of pure ends, an architectural past that always presupposes our present and a future conceived through the blind lens of infinite perfection. It is by drawing from a diverse range of theoretical sources and perspectives that the following paper seeks to critically explore and reframe the idea of architectural history and progress. In particular, this comprises an introductory outline study that begins to question the traditional space of architectures historical subject through a range of theoretical works that inform an alternate historical dynamic of fragmentary, random and terminal moments of past architectural possibility.